Rancang Bangun Alat Pencacah Tandan Kosong Kelapa Sawit Sebagai Bahan Bakar pada Pabrik Semen dan PLTU - Ahmad Qodratillah; Akram Alimin; Anshar, Muhammad; Zubair Sultan, Ahmad (Politeknik Negeri Ujung Pandang, 2026)
Empty palm oil bunches (EPOB) are one of the most abundant solid wastes generated from the palm oil industry, accounting for approximately 30–35% of fresh fruit bunch weight. Despite their availability, their utilization remains suboptimal, particularly as a renewable energy source. This study aims to design, fabricate, and evaluate the performance of an EPOB shredder intended to support co-firing applications in cement plants and coal-fired power plants. The shredder was designed to produce particle sizes of 8–12 cm with an initial target capacity of ±100 kg/h. The research was conducted at the Energy Laboratory of the Mechanical Engineering Department, Politeknik Negeri Ujung Pandang, over a four-month period. Experimental testing was performed at three rotational speeds, namely 1500 rpm, 2000 rpm, and 2500 rpm, to determine the optimal operating condition. The results show that the highest performance was achieved at 2500 rpm, producing a maximum capacity of 381.05 kg/h. Furthermore, the processed EPOB exhibited a calorific value of 4173.54 Cal/kg and a moisture content of 9.4%, indicating its suitability as an alternative fuel for co-firing systems. Although higher rotational speeds increased fuel consumption, the overall performance demonstrated a significant improvement in productivity and fuel quality. The developed shredder effectively enhances the physical characteristics of EPOB, enabling its utilization as a sustainable biomass fuel. This study contributes to waste management strategies and supports the transition toward renewable energy in industrial applications.